Analysis of Motor Vehicle Accidents due to Damaged Roads - Vicki Dwi Purnomo; Surodjo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The obligation to maintain roads has been regulated in Article 24 of the Road Traffic Traffic Law and criminal sanctions in Article 273 of the Road Traffic Traffic Law. Accidents caused by damaged roads occur quite often, but they are still common in society so that accident victims report their losses to the authorities so it is not uncommon to find cases that have advanced to court. This paper aims to find out how law enforcement is against road administrators who are negligent and what factors are the obstacles. case (case approach), while the data sources used are secondary data sources, data collection techniques through library research, and analyzed by qualitative analysis. Based on the results of the study that the review of criminal law in cases of traffic accidents due to the impact of road damage is based on the description of article 273 of Law Number 22 of 2009 concerning Road Traffic and Transportation, the material crime committed by road administrators is a passive crime that does not pure.